Localisation and Isolation of Fungal Endophytes from Healthy Tissue of Stevia rebaudiana (Bert.) - Madhumita Kumari; Sheela Chandra (International Journal of Phytomedicine, 2013)
Endophytes arethe microorganisms living inside the plant tissue without causing any harm tothe host. For past few decades, research community has keen interest inendophyte research as endophytes are able to produce secondary metabolitessimilar to the one produced by host plant, which can be used as potentialtherapeutics against several diseases. Steviarebaudiana (Bert.) is known as a sweetener plant, but besides as sweeteningagent it has many other therapeutic potential and can be used asantihypertensive, anti-tumour, vasodilator and neuroprotective drug. Researchefforts have been made to isolate and identify fungal endophytes from Stevia rebaudiana (Bert.) but no effortshave been taken to study the potential of endophytes for steviol glycosidesproduction. So the present study includes histological studies, isolation andpurification of fungal endophytes from different parts of Stevia rebaudiana (Bert.) plant. Maximum localisation of endophyteswas observed in phloem tissue of stem. Two colonies were purified, each fromstem and leaf tissues showing cream and white morphology respectively. Microscopicstudies revealed long, branched and septate hyphae with club shaped sporangium.